Analisis Pengaruh Nilai Tukar Rupiah dan Produk Domestik Bruto (PDB) Terhadap Neraca Transaksi Berjalan di Indonesia Tahun 2004-2020 - Rexa Ananda (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2022)
This research aims to know how the influence of the rupiah exchange rate, BI rate, and GDP on the current account balance in Indonesian in 2004-2020. This research uses independent variables of The Rupiah Exchange, and Gross Domestic Product (GDP) and dependent variable is The Current Account Balance in Indonesian. The data used in this research is annual data from 2004-2020. The analytical method used in this study is multiple linear regression analysis using the Ordinary Least Square (OLS) method. The results showed that the Rupiah Exchange Rate variable had a negative and insignificant effect on the Current Account Balance in Indonesia for 2004-2020. it also showed that GDP has a significant negative effect on the Current Account in Indonesia in 2004-2020.